Association between Brachycephaly, Chiari Malformation, and Basilar Invagination - Botelho, Ricardo Vieira; Botelho, Pedro Bittencourt; Hernandez, Bruna; Sales, Mauricio Bezerra; Rotta, José Marcus (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background There is evidence that Chiari malformation (CM) and basilar invagination (BI) are largely due to disproportion between the content and volume of the posterior fossa. A recent study identified an increased association between brachycephaly and BI. In several types of craniosynostosis, the posterior fossa volume is smaller than normal, and this is more pronounced in coronal synostosis. The aim of this study is to evaluate the association between CM and BI.Methods The cephalic index (CI) measured on magnetic resonance imaging (MRI) from a sample of patients with craniocervical malformation was compared with that of normal subjects.Results The average CI in the craniovertebral junction malformation (CVJM) group was significantly higher in BI patients than in normal subjects. The BI patients also had the highest CI among the whole sample of patients (p = 0.009).Conclusions In this study, BI patients had the highest CI among patients with CVJM and a significantly higher CI than those in the control group. Our data confirm the association between BI and brachycephaly.
Keywords: platybasia; craniosynostosis; basilar impression; Chiari type I; arnold–chiari malformation